Construction of the Antheraea pernyi (Lepidoptera: Saturniidae) Multicapsid Nucleopolyhedrovirus Bacmid System. Issue 5 (16th September 2020) - Ye, Bo; Zhao, Zhenjun; Yue, Dongmei; Li, Peipei; Wang, Linmei; Zhang, Bo; Fan, Qi
Abstract: In this study, we established the Antheraea pernyi multicapsid nucleopolyhedrovirus (AnpeNPV) bacmid system for the construction of a Bac-to-Bac expression system and the generation of virus mutants. The CopyRight pSMART BAC cloning vector harboring the chloramphenicol resistance gene was introduced into the AnpeNPV genome to produce the AnpeNPV bacmid that could be propagated in Escherichia coli with stable replication. The enhanced green fluorescent protein (EGFP) was successfully expressed in both Tn-Hi5 cells and A. pernyi pupae using the AnpeNPV Bac-to-Bac expression system. To generate the AnpeNPV mutants, we developed the AnpeNPV bacmid/λ Red recombination system that facilitated the deletion of viral genes from the AnpeNPV genome. The genes cathepsin and chitinase were deleted and a derivative AnpeNPV Bac-to-Bac expression system was constructed. Furthermore, we demonstrated that the novel expression system could be used to express human epidermal growth factor in A. pernyi pupae. Taken together, the AnpeNPV bacmid system provides a powerful tool to create the AnpeNPV Bac-to-Bac expression system for protein expression in A. pernyi pupae. Further, it helps to knock-out genes from the AnpeNPV genome with λ Red recombination system for identification of the role of viral genes involved in regulating gene expression, DNA replication, virion structure, and infectivity during the AnpeNPV infection process.